2015
DOI: 10.1109/jestpe.2014.2330951
|View full text |Cite
|
Sign up to set email alerts
|

Power Loss Analysis and Comparison of Segmented and Unsegmented Energy Coupling Coils for Wireless Energy Transfer

Abstract: This paper investigated the power losses of unsegmented and segmented energy coupling coils for wireless energy transfer. Four 30-cm energy coupling coils with different winding separations, conductor cross-sectional areas, and number of turns were developed. The four coils were tested in both unsegmented and segmented configurations. The winding conduction and intrawinding dielectric losses of the coils were evaluated individually based on a well-established lumped circuit model. We found that the intrawindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The application of segmentation capacitors to multi-turn inductors for WPT has only been performed by a limited set of authors: Monti et al [31] presented a 433 MHz WPT system with a 30 mm primary segmented resonator; as the structural optimization algorithm is not detailed and as the efficiency levels for a coil distance of 20 mm are in the range of 1 %, practical applicability is limited. Tang and McDannold [38] evaluated the beneficial effect of capacitive segmentation on large inductors (diameter greater than 10 cm), explicitly denoting the reduction of dielectric losses, but not providing a generalized modeling and optimization approach.…”
Section: ) Capacitively Segmented Coilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of segmentation capacitors to multi-turn inductors for WPT has only been performed by a limited set of authors: Monti et al [31] presented a 433 MHz WPT system with a 30 mm primary segmented resonator; as the structural optimization algorithm is not detailed and as the efficiency levels for a coil distance of 20 mm are in the range of 1 %, practical applicability is limited. Tang and McDannold [38] evaluated the beneficial effect of capacitive segmentation on large inductors (diameter greater than 10 cm), explicitly denoting the reduction of dielectric losses, but not providing a generalized modeling and optimization approach.…”
Section: ) Capacitively Segmented Coilsmentioning
confidence: 99%
“…Equation ( 63) can be used to determine the segmentation capacitors C s,ij based on the elements of the mutual inductance matrix M. In contrast to the approaches given by [30], [31], [38], the segmentation capacitor values are not equal across the coil, but are dependent on the location and effective inductance of individual segments (also see section IV).…”
Section: B Capacitive Coil Segmentationmentioning
confidence: 99%
“…The cage made of polycarbonate, which is the substrate for L21–L25, has a relative permittivity of ε r = 3. Therefore, for the current induced in Tx resonators, λ is 13 m. To ensure the length of each segments is less than λ/10, L21–L25 were segmented into two identical pieces to prevent phase-inversion in the current distribution along L21–L25, which causes EM field cancellation at the location of L4 [33]. …”
Section: Design Of the 4-coil Inductive Linkmentioning
confidence: 99%
“…Zhong et al found a way to make a three-coil wireless energy transfer system more efficient than a two-coil one [ 3 ]. Experiments were also conducted by Tang et al to show the efficiency of wireless energy transfer between unsegmented and segmented coupling coils [ 4 ]. Li et al wrote a paper introducing the potential usage of wireless energy transfer for electrical vehicles [ 5 ].…”
Section: Related Workmentioning
confidence: 99%